DFT/TD-DFT calculations, spectroscopic characterizations (FTIR, NMR, UV–vis), molecular docking and enzyme inhibition study of 7-benzoyloxycoumarin. (April 2018) - Alam, Mahboob; Alam, Mohammad Jane; Azaz, Shaista; Parveen, Mehtab; Park, Soonheum; Ahmad, Shabbir
Graphical abstract: Highlights: FTIR, NMR ( 1 H and 13 C) and UV–vis spectra were measured. Hirshfeld surface analysis. DFT and TD-DFT calculations. Molecular docking and BuChE inhibition. Abstract: The quantum chemical study, spectroscopic characterization and biological activity of the pharmaceutically active 7-benzoyloxycoumarin (2) molecule have been presented. Potential energy surface (PES) scanning has been performed to search for the most stable molecular geometry of the present compound. The stable geometry in the ground state, IR, UV–Vis absorption and NMR ( 13 C, 1 H) spectra of the title compound were theoretically obtained and compared with the experimental one. Various theoretical molecular parameters like molecular energy, atomic charges, dipole moment, thermodynamic parameters, donor-acceptor natural bond orbital (NBO) hyperconjugative interaction energies, frontier molecular orbitals energies, HOMO-LUMO gap, molecular electrostatic potential, chemical reactivity descriptors, molecular polarizability and non-linear optical (NLO) properties are presented. Moreover, the 3D Hirshfeld surfaces and the associated 2D fingerprint plots have been explored. The percentages of various non-covalent interactions are studied and pictorialized by fingerprint plots of Hirshfeld surface. 7-Benzoyloxycoumarin has shown promising inhibitory activity against butrylcholinesterase (BuChE) as compared to the reference drug, galantamine. Molecular docking is carried to introduce compound into the X-ray crystal structures of butrylcholinesterase at the active site to find out the probable binding mode. The results of molecular docking indicated that 7-benzoyloxy derivative of coumarin may show enzyme inhibitor activity.